Pinocytotic engulfment of lipoproteins by macrophages - Miyazaki, Takuro (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is a major cause of acute coronary syndrome and stroke. Foam cell formation in macrophages is involved in controlling plaque stability and the pathogenesis of atherosclerosis. Accordingly, many studies have examined the processes of lipid incorporation, such as scavenger receptor-mediated uptake of oxidized low-density lipoprotein, in cells. In addition to receptor-mediated machinery, growing evidence has suggested that pinocytosis, which is a receptor-independent endocytic pathway, is associated with foam cell formation when a sufficient number of lipoproteins is accumulated around cells. Pinocytotic engulfment of nanoparticles is initiated by plasma membrane ruffling in a phosphatidylinositol-3 kinase-dependent manner. Subsequent to pinosome closure, the majority of pinosomes are internalized through endocytic processes, and they can be recycled into the plasma membrane. These pinocytotic processes are modulated by small GTPases and their cytoskeletal rearrangement. Moreover, pinocytotic abilities may vary between immunological subsets in cells. Accordingly, macrophages may show diverse pinocytotic abilities depending on the surrounding microenvironment. This review summarizes the current understanding of pinocytotic engulfment of lipoprotein in macrophages, and discusses how this endocytic process is governed under hypercholesterolemic conditions.